2017
DOI: 10.1002/anie.201709539
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Bismuth Titanium–Oxo Sulfate Cluster Speciation and Crystallization

Abstract: Inorganic aqueous metal-oxo clusters are both functional "molecular metal oxides" and intermediates to understand metal oxide growth from water. There has been a recent surge in discovery of aqueous Ti-oxo clusters but without extensive solution characterization. We use small-angle and total X-ray scattering, dynamic light scattering, transmission electron microscopy, and a single-crystal X-ray structure to show that heterometals such as bismuth stabilize labile Ti-oxo sulfate clusters in aqueous solution.[Ti … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 48 publications
0
23
0
1
Order By: Relevance
“…During this process, 2 equivalents of H 2 O required for the complete hydrolysis and condensation of the Ti IV precursors like Ti(O i C 3 H 7 ) 4 into TiO 2 are generated in situ by the etherification of isopropanol . Many TOCs of different condensation degrees and structures, also known as prenucleation clusters of TiO 2 nanocrystals, are formed in the mother liquor before TiO 2 formation (Scheme ). In this study, H 2 SSAs are used as additives during the hydrothermal treatment of Ti(O i C 3 H 7 ) 4 .…”
Section: Resultsmentioning
confidence: 99%
“…During this process, 2 equivalents of H 2 O required for the complete hydrolysis and condensation of the Ti IV precursors like Ti(O i C 3 H 7 ) 4 into TiO 2 are generated in situ by the etherification of isopropanol . Many TOCs of different condensation degrees and structures, also known as prenucleation clusters of TiO 2 nanocrystals, are formed in the mother liquor before TiO 2 formation (Scheme ). In this study, H 2 SSAs are used as additives during the hydrothermal treatment of Ti(O i C 3 H 7 ) 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we used Bi 3+ to isolate the Keggin cluster [FeO 4 Fe 12 O 12 (OH) 12 L 12 ] 17− (L=CCl 3 COO − or CF 3 COO − ) from water . These studies showed that Bi stabilizes this reactive iron oxyhydroxide intermediate, and this synthetic strategy was later employed to isolate Ti 4+ polyoxocations, suggesting broader utility . We could not successfully adapt the role of Bi 3+ to other lone pair p‐block metals or Ln 3+ metals in stabilizing and promoting metal oxo cluster growth in water.…”
Section: Figurementioning
confidence: 99%
“…[15,16] These studies showed that Bi stabilizes this reactive iron oxyhydroxide intermediate,a nd this synthetic strategy was later employed to isolate Ti 4+ polyoxocations, suggesting broader utility. [17] We could not successfully adapt the role of Bi 3+ to other lone pair p-block metals or Ln 3+ metals in stabilizing and promoting metal oxo cluster growth in water. Therefore,wemust understand the unique character of bismuth to further exploit it in this role.T owards this goal and also towards determining the reaction pathway from the Fe(aq) monomer to the Fe Keggin ion, we have isolated and structurally characterized af ragment of the Bi-capped iron Keggin ion, Fe 3 BiO 2 (CCl 3 COO) 8 (THF)(H 2 O) 2 (BiFe 3 ).…”
mentioning
confidence: 99%
“…[15,16] These studies showed that Bi stabilizes this reactive iron oxyhydroxide intermediate,a nd this synthetic strategy was later employed to isolate Ti 4+ polyoxocations, suggesting broader utility. [17] We could not successfully adapt the role of Bi 3+ to other lone pair p-block metals or Ln 3+ metals in stabilizing and promoting metal oxo cluster growth in water. Therefore,wemust understand the unique character of bismuth to further exploit it in this role.T owards this goal and also towards determining the reaction pathway from the Fe(aq) monomer to the Fe Keggin ion, we have isolated and structurally characterized af ragment of the Bi-capped iron Keggin ion, Fe 3 BiO 2 (CCl 3 COO) 8 (THF)(H 2 O) 2 (BiFe 3 ).…”
mentioning
confidence: 99%